2016
DOI: 10.4238/gmr.15028222
|View full text |Cite
|
Sign up to set email alerts
|

Role of MTHFR C677T and MTR A2756G polymorphisms in thyroid and breast cancer development

Abstract: ABSTRACT. Folate metabolism is essential for DNA synthesis and repair. Alterations in genes that participate in folate metabolism can be associated with several types of malignant neoplasms, including thyroid and breast cancer. In the present case-control study, we examined the association between methylenetetrahydrofolate reductase (MTHFR C677T, rs1801133) and methionine synthase (MTR A2756G, rs1805087) polymorphisms and risk for thyroid and breast cancer. Polymerase chain reaction-restriction fragment length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Alterations in DNA methylation due to MTHFR polymorphisms may be associated with the development of cancer [74][75][76]. Association studies on MTHR C677T polymorphisms and BC risk were performed in Brazil [77] and Ecuador [78] (Table 5). In both reports, the authors found a significant association between this SNP and BC risk.…”
Section: Other Bc Susceptibility Mutations In Central and South Amerimentioning
confidence: 99%
“…Alterations in DNA methylation due to MTHFR polymorphisms may be associated with the development of cancer [74][75][76]. Association studies on MTHR C677T polymorphisms and BC risk were performed in Brazil [77] and Ecuador [78] (Table 5). In both reports, the authors found a significant association between this SNP and BC risk.…”
Section: Other Bc Susceptibility Mutations In Central and South Amerimentioning
confidence: 99%
“…It has been suggested that the cancer risk associated with MTHFR polymorphisms may be modulated by alcohol intake, but only a few previous studies have examined this issue in detail regarding thyroid cancer risk. A similar Brazilian study was recently conducted to determine the interaction between alcohol consumption and MTHFR C677T on thyroid cancer risk, but the interactive effect was not statistically significant ( P for interaction = 0.84) 38 . The inconsistency between the Brazilian study and the current study may be due to differences in genetic characteristics of the studied populations, which may affect certain biochemical reactions after alcohol consumption; for instance, the ALDH2 genetic variant is prevalent only in East Asians and is associated with an inability to metabolize a carcinogenic alcohol metabolite, acetaldehyde, into acetate 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, exposure to inorganic arsenic may deplete the pool of methyl groups and interfere with folate metabolism with consequences on DNA synthesis and repair. The reduced expression of MTHFR has been previously associated with breast cancer development (53). Conversely, in this study, we noted in MCF7 cells in culture that exposure to NaAs III had a biphasic effect on the expression of FOLR1, a membrane-bound protein involved in transport of folate into cells.…”
Section: Discussionmentioning
confidence: 99%